Klotho Deficiency Accelerates Stem Cells Aging by Impairing Telomerase Activity. (18th November 2018) - Ullah, Mujib; Sun, Zhongjie
Abstract: Understanding the effect of molecular pathways involved in the age-dependent deterioration of stem cell function is critical for developing new therapies. The overexpression of Klotho (KL), an antiaging protein, causes treated animal models to enjoy extended life spans. Now, the question stands: Does KL deficiency accelerate stem cell aging and telomere shortening? If so, what are the specific mechanisms by which it does this, and is cycloastragenol (CAG) treatment enough to restore telomerase activity in aged stem cells? We found that KL deficiency diminished telomerase activity by altering the expression of TERF1 and TERT, causing impaired differentiation potential, pluripotency, cellular senescence, and apoptosis in stem cells. Telomerase activity decreased with KL-siRNA knockdown. This suggests that both KL and telomeres regulate the stem cell aging process through telomerase subunits TERF1, POT1, and TERT using the TGFβ, Insulin, and Wnt signaling. These pathways can rejuvenate stem cell populations in a CD90-dependent mechanism. Stem cell dysfunctions were largely provoked by KL deficiency and telomere shortening, owing to altered expression of TERF1, TGFβ1, CD90, POT1, TERT, and basic fibroblast growth factor (bFGF). The CAG treatment partially rescued telomerase deterioration, suggesting that KL plays a critical role in life-extension by regulating telomere length and telomerase activity.